Understanding the Impact of Chronic Pain in the Emergency Department: Prevalence and Characteristics of Patients Visiting the Emergency Department for Chronic Pain at an Urban Academic Health Sciences Centre - Rebecca N. Small; Yaadwinder Shergill; Steve Tremblay; Jennifer Nelli; Danielle Rice; Catherine Smyth; Patricia A. Poulin (Taylor & Francis Group, 2019)
Background Canadians make approximately 16 million visits to the emergency department (ED) each year. ED visits for non-urgent reasons contribute to suboptimal patient care and ineffective resource use. Aims To estimate the proportion of ED visits related to chronic pain at our institution. Methods. We conducted a retrospective review of 1000 randomly selected ED visits at TOH during the 2012-2013 fiscal year (April 1, 2012 to March 31, 2013). Visits for chronic pain were identified using pre-defined criteria. Demographic and medical data were extracted from medical charts. Results 104 visits during this time period were related to chronic pain (10.4%; 95% CI: 8.2-12.6). All visits were from unique patients (i.e., no patients contributed more than 1 visit). Patients were predominantly women (71%), with a mean age of 45.9 years. Seventy-eight percent of patients had a primary care provider. The most common location of pain included the abdomen (24%), the head or face (21%), and the low back (21%). Only 5% of patients had consultation with a pain medicine specialist while 78% were awaiting a consultation. More than 2/3 of patients (71%) reported using opioids for their pain. Conclusion Presenting to the ED for chronic pain was found to occur among a sample of ED visits reviewed. This can result in ineffective care for patients with chronic pain. Cost-effective solutions to improve clinical outcomes and reduce ED use for chronic pain may yield significant improvements in health outcomes of patients and benefits for the health care system.